2021
DOI: 10.1002/app.50675
|View full text |Cite
|
Sign up to set email alerts
|

Study on char reinforcing of different inorganic fillers for expandable fire resistance silicone rubber

Abstract: Sodium silicate monohydrate (NSH), glass frits (GF) and aluminum hydroxide (ATH) were incorporated into room temperature vulcanized (RTV) silicone rubber (SR) as char reinforcing materials to improve the fire resistance of intumescent flame retardant silicone rubber. SR composites containing only intumescent flame retardant such as phosphorus nitrogen composite flame retardant (NH2‐C) and expandable graphite (EG) were used as comparison samples. Limiting oxygen index (LOI) test, vertical burning test (UL‐94), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The experimental sample preparation method was optimized based on the laboratory‘s prior experience and published articles [22,23] . EBP is a branched polyether polyester polyol with a viscosity of about 3000 m⋅Pa⋅s and a hydroxyl content of 4.7 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental sample preparation method was optimized based on the laboratory‘s prior experience and published articles [22,23] . EBP is a branched polyether polyester polyol with a viscosity of about 3000 m⋅Pa⋅s and a hydroxyl content of 4.7 %.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental sample preparation method was optimized based on the laboratory's prior experience and published articles. [22,23] EBP is a branched polyether polyester polyol with a viscosity of about 3000 m•Pa•s and a hydroxyl content of 4.7 %. First, EBP and 1,4 BD were put into a vacuum drying oven and dried under vacuum at 120 °C for two hours, while fillers such as mica powder, aluminum hydroxide, and EG were placed under vacuum at 150 °C for three hours.…”
Section: Reaction Mechanism Analysis Of Polyurethanementioning
confidence: 99%
“…In our previous research, 21 it was found that the addition of ATH enable the char residue for the intumescent fire-resistant SR composites to maintain a microexpanded complete shape after long time of calcination, while GF could greatly increase the compressive strength of the char. In this study, the effects of three vital elements (GF, ATH, and NH 2 C) on the performance of the ceramizable silicone rubber (CSR) were investigated.…”
Section: Introductionmentioning
confidence: 98%
“…It improves the uniformity of the char layer and endows the porous char layer better mechanical properties. 21 In addition, the distribution of GF in polymer matrices has great effect on both mechanical and flame-retardant properties of CSR composites. During calcination, the molten GF can form compact bulk via adhering to other pyrolysis particles and create a more rigid ceramic char to serve as a reinforcing framework for char residues, which could improve the strength of char residues and durably maintain structural integrity to prevent flame propagation.…”
mentioning
confidence: 99%
“…Consequently, enhancing the electrical conductivity of silicone rubber has emerged as a noteworthy subject commanding attention within the realm of scientific inquiry. 3,4 One of the main benefits of improving the conductivity of silicone rubber is that it can reduce the contact thermal resistance between the heat source surface and the silicone rubber contact surface. For example, conductive silicone rubber can be used as an insulator and electromagnetic interference (EMI) shield in electronic devices.…”
Section: Introductionmentioning
confidence: 99%